The once upon a time world : the dark and sparkling story of the French Riviera - Miles, Jonathan, 1952- (Pegasus Books, Ltd., 2023)
"Chronicling two-hundred years of glamour, intrigue, and hedonism, this rich and vivid history of the French Riviera features a vast cast of characters, from Pablo Picasso and Coco Chanel to Andre Matisse and James Baldwin. 1835, Lord Brougham founded Cannes, introducing bathing and the manicured lawn to the wilds of the Mediterranean coast. Today, much of that shore has become a concrete mass from which escape is an exclusive dream. In the 185 years between, the stretch of seaboard from the red mountains of the Esterel to the Italian border hosted a cultural phenomenon well in excess of its tiny size. A mere handful of towns and resorts created by foreign visitors - notably English, Russian and American - attracted the talented, rich and famous as well as those who wanted to be. For nearly two centuries of creativity, luxury, excess, scandal, war and corruption, the dark and sparkling world of the Riviera was a temptation for everybody who was anybody. Often frivolous, it was also a potent cultural matrix that inspired the likes of Picasso, Matisse, Coco Chanel, Scott Fitzgerald, Cole Porter, James Baldwin, Catherine Mansfield, Sartre and Stravinsky. In Once Upon a Time World, Jonathan Miles presents the remarkable story of the small strip of French coast that lured the world to its shores. It is a wild and unforgettable tale that follows the Riviera's transformation from paradise and wilderness to a pollution imperiled concrete jungle."--Publisher's website.